Tensile Behavior of lignocellulosic reinforced polyester composites: Part III coir fiber - Santafé Júnior,H.P.G. (2010)
The fiber extracted from the husk of a coconut fruit, known as coir fiber, has been extensively investigated as a second phase incorporation into polymer composites. The moderate strength of the coir fiber usually does not represent reinforcement to relatively strong thermoset matrices such as polyester, epoxy and phenolic. However, a selection of thinner coir fibers and a post cure treatment of the composite could improve its mechanical performance. Therefore, this work investigated the tensile properties of post-cured polyester matrix composites incorporated with the thinnest coir fiber. Tensile specimens with up to 40% in volume of long and aligned coir fibers were tested and their fracture analyzed by scanning electron microscopy. A relatively improvement was found in the tensile properties for the amount of 40% of coir fiber. These results were compared with similar composites that were bend-tested. The fracture analysis showed a comparatively better fiber/matrix adhesion.